Renin cells in homeostasis, regeneration and immune defence mechanisms - Gomez, R. Ariel (Nat Rev Nephrol, 2018)
An accumulating body of evidence suggests that renin-expressing cells have developed throughout evolution as a mechanism to preserve blood pressure and fluid volume homeostasis as well as to counteract a number of homeostatic and immunological threats. In the developing embryo, renin precursor cells emerge in multiple tissues, where they differentiate into a variety of cell types. The function of those precursors and their progeny is beginning to be unravelled. In the developing kidney, renin-expressing cells control the morphogenesis and branching of the renal arterial tree. The cells do not seem to fully differentiate but instead retain a degree of developmental plasticity or molecular memory, which enables them to regenerate injured glomeruli or to alter their phenotype to control blood pressure and fluid–electrolyte homeostasis. In haematopoietic tissues, renin-expressing cells might regulate bone marrow differentiation and participate in a circulating leukocyte renin–angiotensin system, which acts as a defence mechanism against infections or tissue injury. Furthermore, renin-expressing cells have an intricate lineage and functional relationship with erythropoietin-producing cells and are therefore central to two endocrine systems — the renin–angiotensin and erythropoietin systems — that sustain life by controlling fluid volume and composition, perfusion pressure and oxygen delivery to tissues. However, loss of the homeostatic control of these systems following dysregulation of renin-expressing cells can be detrimental, with serious pathological events.